MEMBANTU NAGARI MEMBANGUN DI AUR KUNING KECAMATAN PASAMAN KABUPATEN PASAMAN BARAT - Nurmiati Nurmiati; Ossy Y. Prastika; M. Fiqri Fadhlan (BULETIN ILMIAH NAGARI MEMBANGUN, 2019)
Nagari Aua Kuniang is one of the Nagari in Pasaman Subdistrict, West Pasaman Regency, having an area of 13,745 km2 consisting of 6 jorong, Jorong Padang Tujuh, Sukomananti, Pinaga, Lubuak Landua, Bukik Nilam and Lembah Binuang. The Income of the community depend on plantations such as Oil Palm and Cocoa and crops planting such as corn and with existing tourism potential such as mountain tourism, waterfalls and most importantly cultural tourism and religious tourism such as prohibited fish in the Surau Inyiak Lubuak Landua complex, then the development of the Aua Kuniang village is very likely to be developed. The low level of public education is one of the factors that can hinder the development of the nagari. To help nagari Aua Kuniang develop, counseling, training or pilot activities are conducted covering the fields of Nutrition and Health, the Environment, Education, Religion and Culture and the Law and Human Rights, which are carried out through the KKN-PPM program from Andalas University involving students from various study programs. During the program implementation, counseling, training or piloting have been carried out 12 programs in the field of Nutrition and Health, 9 programs in the field Environment, 11 programs in the field of Education, Religion and Culture and Law and 7 programs in the field of Human Rights.